Konsep Pendidikan Karakter Islami dalam Literatur Klasik: Telaah Kritis Kitab Washaya Al-Abā Li Al-Abnā - Moh. Syaeful Ulum; Ade Suryadi; Sri Utami Dewi; Asep Saripulloh; Tanti Sulastini (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study deeply examines and deconstructs the concept of Islamic education, with a specific focus on character education, as contained in the classical literature Washaya al-Abā li al-Abnā by Sheikh Muhammad Shakir al-Iskandari. Amidst the vortex of moral crisis, moral degradation, and value disorientation massively hitting the younger generation in the current era of digital disruption, character education occupies a position as a primary urgency and the nation's moral bulwark. Through a qualitative-philosophical approach with a comprehensive library research method, this study hermeneutically analyzes the textual contents of the book, to then draw its relevance to the context of the dynamics of Islamic education in contemporary Indonesia. The results of the study indicate that this book contains 20 pieces of advice that holistically and structurally discuss essential character values, stretching from the theological and social realms to the personal and academic realms. The internalization of values from this book is believed to act as a catalyst to support the realization of the vision of creating a generation that is not only cognitively superior, but also possesses holistic character, noble morals, and moral resilience amidst the challenges of globalization.